2022
DOI: 10.1038/s41467-022-32129-y
|View full text |Cite
|
Sign up to set email alerts
|

Tectonically-driven oxidant production in the hot biosphere

Abstract: Genomic reconstructions of the common ancestor to all life have identified genes involved in H2O2 and O2 cycling. Commonly dismissed as an artefact of lateral gene transfer after oxygenic photosynthesis evolved, an alternative is a geological source of H2O2 and O2 on the early Earth. Here, we show that under oxygen-free conditions high concentrations of H2O2 can be released from defects on crushed silicate rocks when water is added and heated to temperatures close to boiling point, but little is released at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…4 ) ( Fig. 1 C ) ( 26 , 51 , 56 , 57 ). In this case, the oxygen atoms in •OH and H 2 O 2 ultimately originate from water ( Fig.…”
Section: Possible Mechanisms For H 2 O 2...mentioning
confidence: 98%
See 2 more Smart Citations
“…4 ) ( Fig. 1 C ) ( 26 , 51 , 56 , 57 ). In this case, the oxygen atoms in •OH and H 2 O 2 ultimately originate from water ( Fig.…”
Section: Possible Mechanisms For H 2 O 2...mentioning
confidence: 98%
“…Stress-induced ROS generation at silicate–water interfaces in several geological processes has been investigated ( 25 , 26 , 51 ). Experiments mimicking abrasion of quartz in turbulent subaqueous environments indicate that a significant amount of H 2 O 2 could be produced, creating and sustaining oxic microenvironments in Archean deltas and seashores ( 25 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also indicate rock comminution can act as a source of NH4 + to the subglacial system. Crushing of glacial rock samples in the ball mill generates heat (Stone et al, 2022), which might have contributed to the NH4 + measured. However, there was no correlation between NH4 + and %N or %OC in the samples.…”
Section: Erosion As a Source Of Ammonium For Nitrifiersmentioning
confidence: 99%
“…These have primarily focused on the potential reactivity of silicates after comminution (Gill-Olivas et al, 2021;Telling et al, 2015) and the release or production of gases during comminution (Gill-Olivas et al, 2021;Macdonald et al, 2018). It has been shown that comminution of certain rocks and minerals can generate strong redox agents, such as H2 (Saruwatari et al, 2004;Takehiro et al, 2011;Telling et al, 2015;Wakita et al, 1980;Edgar et al, 2022) and H2O2 (Bak et al, 2017;Borda et al, 2003;He et al, 2021;Edgar et al, 2022;Stone et al, 2022). These are expected to have an https://doi.org/10.5194/egusphere-2022-908 Preprint.…”
Section: Introductionmentioning
confidence: 99%